Replacement of diaminopimelic acid by cystathionine or lanthionine in the peptidoglycan of Escherichia coli. - Mengin-Lecreulx, D. (American Society for Microbiology (ASM), 1994)
In Escherichia coli, auxotrophy for diaminopimelic acid (A2pm) can be suppressed by growth with exogenous cystathionine or lanthionine. The incorporation of cystathionine into peptidoglycan metabolism was examined with a dapA metC mutant, whereas for lanthionine, a dapA metA mutant strain was used. Analysis of peptidoglycan precursors and sacculi isolated from cells grown with epimeric cystathionine or lanthionine showed that meso-A2pm was totally replaced in the same position by either sulfur-containing amino acid. Moreover, mainly L-allo-cystathionine (95%) or meso-lanthionine (93%) was incorporated into the precursors and sacculi. For this purpose, a new, efficient high-pressure liquid chromatography (HPLC) technique for analysis of the cystathionine isomers was developed. The formation of the UDP-MurNAc tripeptide appeared to be a critical step, since the MurE synthetase accepted meso-lanthionine or D-allo- or L-allo-cystathionine in vitro as good substrates, although with higher Km values. Presumably, the 10-fold-higher UDP-MurNAc-L-Ala-D-Glu pool of cells grown with cystathionine or lanthionine ensured a normal rate of synthesis. The kinetic parameters of the MurF synthetase catalyzing the addition of D-alanyl-D-alanine were very similar for the meso-A2pm-,L-allo-cystathionine-, and meso-lanthionine-containing UDP-MurNAc tripeptides. HPLC analysis of the soluble fragments resulting from 95% digestion by Chalaropsis N-acetylmuramidase of the peptidoglycan material in isolated sacculi revealed that the proportion of the main dimer was far lower in cystathionine and lanthionine sacculi.